Answer: 6 + n = 6n
Step-by-step explanation:
Answer:
![f(x) = -2x^2 + 7x + 9](https://tex.z-dn.net/?f=f%28x%29%20%3D%20-2x%5E2%20%2B%207x%20%2B%209)
Step-by-step explanation:
![f(x) = ax^2 + bx + c\\f(0) = 9 => c = 9;\\f(2) = 15 = 4a + 2b + 9 2a + b = 3\\f(3) = 9a + 3b + 9 = 12 3a + b = 1\\Subtract the second equation from the first:\\-a = 2 => a = -2; b = 7; c = 9\\f(x) = -2x^2 + 7x + 9](https://tex.z-dn.net/?f=f%28x%29%20%3D%20ax%5E2%20%2B%20bx%20%2B%20c%5C%5Cf%280%29%20%3D%209%20%3D%3E%20c%20%3D%209%3B%5C%5Cf%282%29%20%3D%2015%20%3D%204a%20%2B%202b%20%2B%209%20%3C%3D%3E%202a%20%2B%20b%20%20%3D%203%5C%5Cf%283%29%20%3D%209a%20%2B%203b%20%2B%209%20%3D%2012%20%3C%3D%3E%203a%20%2B%20b%20%3D%201%5C%5CSubtract%20the%20second%20equation%20from%20the%20first%3A%5C%5C-a%20%3D%202%20%3D%3E%20a%20%3D%20-2%3B%20b%20%3D%207%3B%20c%20%3D%209%5C%5Cf%28x%29%20%3D%20-2x%5E2%20%2B%207x%20%2B%209)
Answer:
363 feet
Step-by-step explanation:
330 ft / 10 seconds = 33 ft per second
33 * 11 seconds = 363 feet
Answer:
B or 31r-71
Step-by-step explanation:
First, use distributive property to expand the first term.
30r-66-(5-r)
Remove the parenthesis of the third term:
30r-66-5+r
Combine like terms
31r-71
Answer:
I think the answer would be +15.
Step-by-step explanation: